Four-dimensional flow magnetic resonance imaging and ultrasound assessment of cerebrospinal venous flow in multiple sclerosis patients and controls. Issue 4 (April 2017) - Schrauben, Eric M; Kohn, Sarah; Macdonald, Jacob; Johnson, Kevin M; Kliewer, Mark; Frost, Sam; Fleming, John O; Wieben, Oliver; Field, Aaron
A possibly causal relationship between multiple sclerosis and chronic cerebrospinal venous insufficiency has recently been hypothesized. Studies investigating chronic cerebrospinal venous insufficiency have reported conflicting results and few have employed multiple diagnostic imaging modalities across a large patient and control population. In this study, three complementary imaging modalities were used to investigate the chronic cerebrospinal venous insufficiency hypothesis in patients with multiple sclerosis and two age- and sex-matched control groups: healthy volunteers and patients with other neurological diseases. Strictly blinded Doppler ultrasound according to the original chronic cerebrospinal venous insufficiency hypothesis; four-dimensional flow magnetic resonance imaging of venous flow in the head, neck, and chest; and contrast-enhanced magnetic resonance venography for neck and chest venous luminography were acquired. An internal jugular vein stenosis evaluation was also performed across modalities. Percentage of subjects meeting ultrasound-based chronic cerebrospinal venous insufficiency criteria was small and similar between groups. In group-wise and pairwise testing, no four-dimensional flow magnetic resonance imaging variables were statistically significantly different, for any measurement location. In contrast-enhanced magnetic resonance venography of the internal jugular and azygos veins, no statistically significant differences were observed in stenosis scores between groups. These results represent compelling evidence against the chronic cerebrospinal venous insufficiency hypothesis in multiple sclerosis.